2004
DOI: 10.1097/00003727-200401000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Health Status by Homeless US Veterans

Abstract: Perceptions of health status among 331 homeless veterans and homeless nonveterans were examined. Homeless veterans were significantly less apt to perceive their health as fair/poor (8%) compared to non-veteran homeless men (19%). Homeless veterans were also more likely to report having a regular source of care (57% versus 36%). Logistic regression analysis indicated the adjusted odds of fair/poor health were more than two times greater for persons reporting depressive symptomatology than for those without this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Nayamathi et al. suggest “the use of health services promotes a greater sense of awareness, which in turn amplifies awareness/perceptions of need for health services” (9). This may also apply to our finding that those homeless veterans who participated in the CWT program had a decline in their GOHAI scores at follow‐up, as this group of veterans received mostly emergency dental care.…”
Section: Discussionmentioning
confidence: 99%
“…Nayamathi et al. suggest “the use of health services promotes a greater sense of awareness, which in turn amplifies awareness/perceptions of need for health services” (9). This may also apply to our finding that those homeless veterans who participated in the CWT program had a decline in their GOHAI scores at follow‐up, as this group of veterans received mostly emergency dental care.…”
Section: Discussionmentioning
confidence: 99%
“…36 The 20-item self-report instrument is designed to measure depressive symptomatology in the general population and has been validated for use in homeless populations. 37 Each item measures the frequency of a symptom on a four-point response scale from 0 ("Rarely or none of the time [Less than one day]") to 3 ("Most of the time [five to seven days]"). Item scores were summed, giving an overall scale that could range from 0 to 60.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, research indicates that perceptions of health vary among the homeless population. A study by Nyamathi et al . (2004) with a sample of 331 homeless individuals indicated that those who are US veterans perceived their health as less favourable than those who were non‐veterans.…”
Section: Introductionmentioning
confidence: 99%